The greater trochanter triangle; a pathoanatomic approach to the diagnosis of chronic, proximal, lateral, lower pain in athletes. Issue 2 (19th November 2008) - Falvey, E C; Franklyn-Miller, A; McCrory, P R
Abstract : Chronic pain experienced in the proximal, lateral, lower limb may arise from the femoro-acetabular joint, from the muscles and tendons that act upon it, from any of the structures that traverse the area, and from more remote structures such as the lumbar spine. The aetiology of pathology in this area is not confined to either trauma or overuse. As a result many different sporting activities may have a causal role. Without a clear clinical/pathological diagnosis, the subsequent management of chronic groin pain is difficult. The combination of complex anatomy, variability of presentation and the non-specific nature of the signs and symptoms makes the diagnostic process problematic. The paper proposes a novel educational model based on pathoanatomic concepts. Anatomical reference points were selected to form a triangle, which provides the discriminative power to restrict the differential diagnosis, and form the basis of ensuing investigation. This paper forms part of a series addressing the three-dimensional nature of proximal lower limb pathology. The 3G approach (groin, gluteal, and greater trochanter triangles) acknowledges this, permitting the clinician to move throughout the region, considering pathologies appropriately.